Impact of Surgical Margin on the Prognosis of Early Hepatocellular Carcinoma (≤5 cm): A Propensity Score Matching Analysis - Wang, Han; Yu, Hua; Qian, You-Wen; Cao, Zhen-Ying; Wu, Meng-Chao; Cong, Wen-Ming (Frontiers in Medicine, 2020)
Aim: The influence of surgical margin on the prognosis of patients with early solitary hepatocellular carcinoma (HCC) (≤5 cm) is undetermined. Methods: The data of 904 patients with early solitary HCC who underwent liver resection were collected for recurrence-free survival (RFS) and overall survival (OS). Propensity score matching (PSM) was performed to balance the potential bias. Results: Log-rank tests showed that 2 mm was the best cutoff value to discriminate the prognosis of early HCC. Liver resection with a >2 mm surgical margin distance (wide-margin group) led to better 5-year RFS and OS rate compared with liver resection with a ≤2 mm surgical margin distance (narrow-margin group) among patients both before (RFS: 59.1% vs. 39.6%, P < 0.001; OS: 85.3% vs. 73.7%, P < 0.001) and after PSM (RFS: 56.3% vs. 41.0%, P < 0.001; OS: 83.0% vs. 75.0%, P = 0.010). Subgroup analysis showed that a wide-margin resection significantly improved the prognosis of patients with microvascular invasion (RFS: P < 0.001; OS: P = 0.001) and patients without liver cirrhosis (RFS: P < 0.001; OS: P = 0.001) after PSM. Multivariable Cox regression analysis revealed that narrow-margin resection is associated with poorer RFS [hazard ratio (HR) = 1.781, P < 0.001), OS (HR = 1.935, P < 0.001], and early recurrence (HR = 1.925, P < 0.001). Conclusions: A wide-margin resection resulted in better clinical outcomes than a narrow-margin resection among patients with early solitary HCC, especially for those with microvascular invasion and without cirrhosis. An individual strategy of surgical margin should be formulated preoperation according to both tumor factors and background liver factors.